Studi Komparasi Pemikiran K. H Ahmad Dahlan dan Prof. Dr. H. Abdul Malik Karim Amrullah dalam Pendidikan Akhlak - Lona Mardiati; Gusnita Gusnita; Najmi Nawry; Ahmad Sabri; Rully Hidayatullah (LPPM Politeknik Pratama, 2024)
The purpose of this research is to explain the comparative study of the Thought of K. H Ahmad Dahlan and Prof. Dr. H. Abdul Malik Karim Amrullah in Moral Education. The method used in this study uses a method or library approach (library research), that library or library study can be defined as a series of activities related to library data collection methods, reading and recording and processing research materials. The results of this study indicate that the comparison of the thoughts of K. H Ahmad Dahlan and Prof. Dr. H. Abdul Malik Karim Amrullah in moral education is as follows: The concept of moral education in the perspective of KH Ahmad Dahlan based on high values and noble life is expected to form a more perfect student's personality, both related to the potential of reason, feelings and actions. While the concept of moral education according to Abdul Malik Karim Amrullah is inseparable from the nature of Islamic education itself which is guided by the Qur'an and sunnah. Moral education seeks to shape the character, character, morals and human personality so that it is able to distinguish between good and bad, right and wrong. According to Abdul Malik Karim Amrullah, moral education is defined as an effort to form knowledge in humans that functions to run life to be able to open human eyes to always have knowledge and have a far and broad view of the future.